Carbonic Anhydrase 12 Protects Endplate Cartilage From Degeneration Regulated by IGF-1/PI3K/CREB Signaling Pathway - Zhao, Xing; Shen, Panyang; Li, Haidong; Yang, Yute; Guo, Jiandong; Chen, Shuai; Ma, Yan; Sheng, Jiamin; Shen, Shuying; Liu, Gang; Fang, Xiangqian (Frontiers in Cell and Developmental Biology, 2020)
Lumbar intervertebral disc degeneration (IVDD) is the most common cause of low back pain. Among all the factors leading to IVDD, lumbar cartilage endplate (LCE) degeneration is considered a key factor. In the present study, we investigated the effect and regulation of carbonic anhydrase 12 (CA12) in LCE, which catalyzes hydration of CO2 and participates in a variety of biological processes including acid-base balance and calcification. Our results showed that CA12, down-regulated in degenerated LCE, could maintain anabolism and prevent calcification in the endplate. Furthermore, CA12 was regulated by IGF-1/IGF-1R/PI3K/CREB signaling pathway. When we overexpressed CA12 in LCE, the decreased anabolism induced by inflammatory cytokine could be rescued. In contrast, reducing CA12 expression, either with siRNA, PI3Kinhibitor or CREB inhibitor, could downregulate anabolism and cause apoptosis and then calcification in LCE. The protective effects of IGF-1 were even diminished with low-expressed CA12. Similar results were also obtained in ex vivo model. Consequently, our results revealed a novel pathway, IGF-1/IGF-1R/PI3K/CREB/CA12, that took a protective role in LCE degeneration by maintaining anabolism and preventing calcification and apoptosis. This study proposed a novel molecular target, CA12, to delay LCE degeneration.